(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2022)
This article aims to analyze the discursive construction of the movement Gays com Bolsonaro through its Twitter profile (@gaycombolsonaro). From their discursive practices, we illuminate their alliances with elements of heterocisexism (BORRILLO, 2010; JUN, 2018) and the consequent legitimation of this ideology. Based on the Discourse Analysis (ROCHA, 2014) and on the tweets and retweets of this self-titled “new LGBT movement”, we point out how the formation of this online discursive network – constitutive of this movement – has, as one of its bases, the polemic negation (DUCROT, 1987) that it establishes in relation to the previous movements. In this sense, we note the construction of a type of nationalist discourse that is produced in opposition to the discussions and agendas of the LGBTI movement, contributing to its erasure.